Increasing School Administrative Staff Effectiveness Through Technology – Based Training Programs and Career Path Mapping - Satriatama, Dandy Aditya; Sunarni, Sunarni; Sultoni, Sultoni (Universitas Negeri Malang, 2024)
The effectiveness of school administrative staff has a very important role in supporting the smooth running of educational operations. However, in fact, there are still many shortcomings in terms of motivation and productivity of TAS (School Administration Staff) employees which cause their performance in the field to not be optimal due to the lack of professional scale training and career path mapping before they are officially assigned. Based on this, the aim of writing this article is to analyze how to increase the effectiveness of school administration staff through technology-based training programs and career path mapping. Then, this article uses an interpretive qualitative approach and literature to streamline mechanisms and speed up the discovery of new steps according to developments in the current era. Data was collected by reading various library sources and qualitative analysis sourced from various types of literature according to the object of study in the form of collecting and analyzing data through bibliographic annotation techniques accompanied by carrying out neat and structured reviews. The results of this research have shown that technology-based training can significantly improve the technical skills of administrative staff, especially in data management and use of administrative software. Apart from that, career path mapping has also been proven to be able to increase job satisfaction and their motivation to develop more professionally in the future. In the end, the combination of accurate training and clarity in career mapping will result in increased productivity and work efficiency of TAS employees. Therefore, the author recommends that all schools continue and consistently develop technology-based training programs accompanied by systematic career path mapping in order to increase the effectiveness of all school administration staff in this country.